Estimation of the Probability to Target Attainment to the Pharmacokinetic/ Pharmacodynamic Index of Ertapenem in Elderly Inpatients - Palma, Daniel; Vega, Elena; Gai, María (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Infectious diseases are one of the most causes of hospitalization and death in adults in the elderly and this population is prone to develop complications and pharmacokinetic/pharmacodynamic changes. Objectives: To estimate the probability to target attainment (PTA) to the pharmacokinetic/pharmacodynamic (PK/ PD) index of ertapenem for older adults hospitalized in a medical ward. Materials and Methods: In a prospective and observational analysis, free drug concentrations of ertapenem were determined in older adults hospitalized at medical ward setting and compared with EUCAST epidemiological cut-off values (ECOFF: 0.064 mg/L) to extreme MIC (64 mg/L), using 1000 Monte Carlo simulations to estimate therapeutic target attainment (%f T ≥ MIC ≥ 40%). Results: Five elderly inpatients with renal impairment and hypoalbuminemia were included with eight samples per patient (n=40 observations). Monte Carlo simulations shown free ertapenem concentrations attain to PK/PD index on the MIC interval from 0.064 to 4 mg/L. Conclusion: If pathogen MICs are ≥ 4 mg/L, elderly inpatients could not attain to the PK/PD target of ertapenem in medical ward setting, rising probability of antimicrobial resistance and therapeutic failure in this population.
Keywords: Elderly; Ertapenem; Pharmacokinetics; Probability to target attainment; PK/; PD index